Community-Based Health Insurance and Out-of-Pocket Healthcare Spending in Africa: Evidence from Rwanda - Andinet Woldemichael; Daniel Zerfu Gurara; Abebe Shimeles (Institute for the Study of Labor (IZA), 2016)
In the absence of third party and prepayment systems such as health insurance and tax-based healthcare financing, households in many low-income countries are exposed to the financial risks of paying large medical bills from out-of-pocket. In recent years, community based health insurance schemes have become popular alternatives to fill such void in the healthcare financing systems. This paper investigates the impact of these schemes on out-of-pocket spending based on three rounds of nationally representative data from Rwanda. We estimate an Extended Two-Part Model to address endogeniety in insurance enrollment and censoring in healthcare expenditure data. We find that community based health insurance program has non-linear and mixed impacts on out-of-pocket expenditure. While the program significantly increases the probability of overall spending, it decreases the amount of per capita spending on healthcare. The program also significantly reduces spending on drug but increases outpatient spending with no detectable impact on inpatient services. Furthermore, we find notable heterogeneity in treatment effects in which households in the top income distribution realize the highest reduction in out-of-pocket spending.
Keywords: C21; C34; D04; I13; I15; 330; impact; health insurance; out-of-pocket; low-income; endogeneity